Bacteria isolated from the stools of Alzheimer's disease patients exacerbate cognitive impairment in 3xTg AD mouse model: Molecular and cell biology/others. (7th December 2020) - Marizzoni, Moira; Tournier, Benjamin; Pauis, Arthur; Millet, Philippe; Mirabelli, Peppino; Salvatore, Marco; Cattaneo, Annamaria; Frisoni, Giovanni B.
Abstract: Background: Human microbiota‐associated (HMA) murine models are developed by gavaging mice with human bacteria or stools and are increasingly used to study the relation between the human microbiota and disease. The aim of this study is to evaluate the effect of gut bacteria isolated from donors with or without Alzheimer's dementia on behavior in AD transgenic (Tg) mice. Method: Sixty female, one‐year 3xTg mice (APP SWE, PS1 M146V and Tau P301L ) received (1) antibiotic treatment (for 14 days before the first gavage), (2) stomach acid suppressant administration, (3) laxative administration (immediately before the first gavage) and, (4) microbiota transplantation (or saline, once every 2 weeks for 2 months). The transplanted microbiota consisted of bacteria isolated from stools of donors pertaining to four different profiles: i) amyloid positive AD patient, amyloid negative cognitively healthy subjects ii) with or iii) without protective APOE genotype and, iv) young healthy donor. As additional control, we included a group of mice that received bacteria isolated from stools of untreated 3xTg mice. Stools collection and behavioral assessment (open‐field test, Y‐maze test, radial maze test, elevated plus maze test) was performed before antibiotic treatment and at day 3, 30, 60 after the first gavage. All mice were sacrificed at day 60 for ex‐vivo assessments. Result: After 60 days from the first gavage, the bacteria from the AD patient induced AD‐like behavior in 3xTg mice, including impaired general activity in the open‐field test and exacerbated anxiety in the elevated plus maze test, compared with mice that received saline or bacteria from untreated 3xTg mice. The bacteria from the other human donors did not influence mouse behavior. Conclusion: The microbiota of AD patients induced an AD‐like phenotype in 3xTg mice. Brain and gut ex‐vivo assessments, 16S rRNA gene sequencing as well as behavioral longitudinal analysis are on‐going to evaluate the human microbiota transplantation efficiency and its effect on AD pathology and inflammation.